2018
DOI: 10.21472/bjbs.051015
|View full text |Cite
|
Sign up to set email alerts
|

GCMS, phytochemicals and antioxidant activities of in vitro callus extracts of Strobilanthes kunthiana (Nees) T. Anderson ex Benth: An endemic plant of Acanthaceae

Abstract: Strobilanthes kunthiana (Neelakurinji) is an endemic and underexploited plant belongs to the Family Acanthaceae. The aim of our study was to evaluate phytochemical analysis, GC-MS analysis and antioxidant activity of in vitro callus extract of Strobilanthes kunthiana. In this present study the phytochemical analysis of various extract of S. kunthiana in vitro callus were studied. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, glycosides, saponins, tannins, steroids, terpenoids and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Since these two species were analyzed for the first time, the high protective efficacy was in consistent with the previously reported species of the genus [14,15] . Strobilanthes has been suggested as a herbal alternative after proper analysis of antioxidants in it [16] . The herbal tea from dried leaves increased the defense system and reduced the blood glucose level [17,18] .…”
Section: Resultsmentioning
confidence: 99%
“…Since these two species were analyzed for the first time, the high protective efficacy was in consistent with the previously reported species of the genus [14,15] . Strobilanthes has been suggested as a herbal alternative after proper analysis of antioxidants in it [16] . The herbal tea from dried leaves increased the defense system and reduced the blood glucose level [17,18] .…”
Section: Resultsmentioning
confidence: 99%
“…The principle compounds were lupeol, Betulin, 9,12-octadecadienoic acid, hexadecenoic acid, methyl ester, 9-octadecenoic acid, methyl ester, alpha-amyrin, β-sitosterol, 4-amino-tetrahydro-2H-pyran-3,5-diol, Decahydro-1,1,4a,8-tetramethyl phenanthren-2 (1H,3H,4Bh)-one, (Dheptadecanoic acid, 16-methyl-methyl ester, 2,6-bis (1,1-dimethylethyl0-4-methylphenol, 3-methyl-2-ketobutyric acid, 2,2,3,4-tetramethyl-5-hexen-3-ol, N-(tertbutoxycarbonyl)-2(-methoxyphenyl) allylamine, cyclotrisiloxane, hexamethyl, benzene sulfonamide (Fig. 3) [4]. Whereas, phytoconstitiutents lupeol and Botulin were found in larger concentration, Hence, this research approaches to target cancer because cancer is one of the leading causes of death worldwide, and the pain associated with it is very intense.…”
Section: Phytoconstituentsmentioning
confidence: 99%
“…The Western Ghats valleys, where this unusual plant was found, are a popular destination for tourists [3]. S. kunthiana leaf callus extract in vitro provides a crucial component for pharmacological activity [4]. Acute respiratory in ammation, gastrointestinal disorders, rheumatism, anxiolytic, anti-diabetic, laxative, anticancer, diuretic, anti-arthritic, and anti-in ammatory activities [5].…”
Section: Introductionmentioning
confidence: 99%
“…8 Everlyne et al 9 studied FT-IR and GC-MS analysis of ethanolic leaves extract of S. kunthianus and reported that it may contains aromatic hydrocarbons, straight chain primary alcohols, fatty acids, alkenes, phenolic compounds, titerpene alcohols and triterpenes, primary aliphatic alcohols and trienoic fatty acids. Prabakaran and Kirutheka 10 identified ten phytoconstituents based on GC-MS analysis in callus methanolic extract of S. kunthianus and studied for antioxidant properties. However, so far there is no phytoconstituents are isolated individually in various plant parts of S. kunthianus.…”
Section: Introductionmentioning
confidence: 99%